Integral Newton-Type Polynomials with Continual Nodes - Kashpur, O. F.; Makarov, V. L.; Khlobystov, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We construct an integral Newton-type interpolation polynomial with a continual set of nodes. This interpolant is unique and preserves an operator polynomial of the corresponding degree.